The Effect of Phosphodiesterase-type 5 Inhibitors on Erectile Function: An Overview of Systematic Reviews - Pyrgidis, Nikolaos; Mykoniatis, Ioannis; Haidich, Anna-Bettina; Tirta, Maria; Talimtzi, Persefoni; Kalyvianakis, Dimitrios; Ouranidis, Andreas; Hatzichristou, Dimitrios (Frontiers in Pharmacology, 2021)
Background: Multiple systematic reviews explore the effect of phosphodiesterase type 5 (PDE5) inhibitors on erectile dysfunction (ED), with each study addressing specific outcomes. However, physicians and policymakers require a holistic approach of this topic. Objective: To summarize the current evidence regarding the efficacy and safety of PDE5 inhibitors for the management of ED through an overview of systematic reviews. Methods: Studies were identified by searching PubMed, Web of Science, Cochrane Library and Scopus databases, as well as sources of grey literature until June 12, 2021 (PROSPERO: CRD42020216754). We considered systematic reviews, meta-analyses or network meta-analyses of randomized trials that provided outcomes about the efficacy and safety of any approved PDE5 inhibitor (avanafil, sildenafil, tadalafil and vardenafil). We constructed forest plots for meta-analytic effects regarding the change in erectile function, adverse events and dropouts after administration of PDE5 inhibitors in the general population and in specific patient groups. Results: We included 23 studies with 154,796 participants and a total of 258 meta-analytic effects. Sildenafil 25mg (Weighted Mean Difference (WMD): 13.08, 95% Confidence Interval (CI): 10.1-16.06) seemed to be statistically superior to all interventions in improving erectile function compared to placebo, but studies with low-dose sildenafil are lacking. Moreover, comparing among different PDE5 inhibitors, sildenafil 50mg or sildenafil 100mg were considered the most effective compounds in the general population. The latter derived, however, predominantly from indirect comparisons among different PDE5 inhibitors. Still, sildenafil 100mg was associated with more treatment-related adverse events and dropouts. Interestingly, low-dose daily tadalafil may be more effective than high-dose on-demand tadalafil (WMD: 1.24, 95% CI: 0.03-2.44). Furthermore, testosterone and PDE5 inhibitors in patients with ED and hypogonadism seem to further improve symptoms, while the addition of a-blockers in patients with urinary symptoms treated with PDE5 inhibitors does not provide additional benefits (WMD: -0.8, 95% CI: -1.65-0.06). Conclusions: Although the efficacy and safety of PDE5 inhibitors, compared to placebo, is well-documented, the existing evidence comparing different PDE5 inhibitors is low. Therefore, high-quality, head-to-head, trials comparing different PDE5 inhibitors are necessary to determine their ideal dosage and formulation based on their safety and efficacy profile.